2022
DOI: 10.1123/jcsp.2021-0035
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Profiles of Danish Youth Soccer Players: The Influence of Gender and Career Development

Abstract: The purpose of this study was (a) to investigate gender differences in mental health among Danish youth soccer players, (b) to discover the mental health profiles of the players, and (c) to explore how career progression and mental health are related. A total of 239 Danish youth elite soccer players (M = 16.85, SD = 1.09) completed an online questionnaire assessing mental well-being, depression, anxiety, along with other background variables. Female players scored significantly lower on mental well-being and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
1
10
0
1
Order By: Relevance
“…While participants demonstrated a normal level of depressive symptoms in the preintervention assessment, the level of depressive symptoms had dropped in post-measurement, in line with previous studies showing that ACT is effective in decreasing symptoms of depression (Räsänen et al, 2016). This finding is promising, since depression is one of the most common mental health challenges and barrier to female soccer players' well-being (Prinz et al, 2016;Küttel et al, 2021). Overall, it seems that the start of the competitive season did not affect general well-being, as no significant within-group changes were observed in CON in other variables than sports-related well-being.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While participants demonstrated a normal level of depressive symptoms in the preintervention assessment, the level of depressive symptoms had dropped in post-measurement, in line with previous studies showing that ACT is effective in decreasing symptoms of depression (Räsänen et al, 2016). This finding is promising, since depression is one of the most common mental health challenges and barrier to female soccer players' well-being (Prinz et al, 2016;Küttel et al, 2021). Overall, it seems that the start of the competitive season did not affect general well-being, as no significant within-group changes were observed in CON in other variables than sports-related well-being.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, it is important to promote sports-related mental health. Special attention is needed for youth players, as Küttel et al, (2021) showed that scores of anxiety, stress, and depressive symptoms increased when progressing in age, highlighting the transition from junior to senior, but also demands from other life domains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Así, Wolanin et al (2016) encuentran diferencias significativas en la prevalencia de síntomas depresivos entre hombres y mujeres, donde éstas muestran 1,84 veces más riesgo que los deportistas masculinos de presentar síntomas clínicamente relevantes. Kuettel et al (2021) analizaron las diferencias de género en la salud mental entre los jóvenes futbolistas daneses y cómo se relacionan la progresión profesional y la salud mental, evaluando el bienestar mental, la depresión, la ansiedad y otras variables. Las jugadoras puntuaron significativamente más bajo en bienestar mental y tenían cuatro veces más probabilidades de expresar síntomas de ansiedad y depresión que los hombres.…”
Section: Discussionunclassified
“…Additionally, within 607 male soccer players, 9% reported alcohol misuse, 38% anxiety and depression, and 58% adverse nutrition (Gouttebarge, Aoki, et al, 2015). The prevalence may also vary upon age (Kuettel, Durand‐Bush & Larsen, 2021), as higher rates of depression (15 vs. 6.6%) and lower psychological wellbeing (PWB) (48 vs. 52) in youth vs. senior male soccer players have been reported (Abbott et al, 2019; Grimson et al, 2021).…”
Section: Introductionmentioning
confidence: 99%